In-Situ Detection of C-Reactive Protein Using Silicon Nanowire Field Effect Transistor - Kwon, Soon Mook; Kang, Gil Bum; Kim, Yong Tae; Kim, Young-Hwan; Ju, Byeong-Kwon (AMER SCIENTIFIC PUBLISHERS, 2011)
Label-free, sensitive, and real-time c-reactive protein (CRP) sensor was fabricated using p-type silicon nanowire (SiNW) based structures configured as field effect transistors (FET) using the conventional 'top-down' semiconductor processes. The width of SiNWs were distributed 80 nm to 400 nm. Among them to improve signal-to-noise ratio and sensitivity of SiNW FET, 221 nm-SiNW was chosen for biosensing of CRP. Antibody of c-reactive protein (anti-CRP) was immobilized on the SiNW surface through polydimethylsiloxane (PDMS) microfluidic channel for detection of CRP. Specific binding of CRP with anti-CRP on the SiNW surface caused a conductance change of SiNW FET and various injections from 10 and 1 mu g/ml to 100 ng/ml solutions of CRP resulted in the conductance changes from 39 and 25 to 16%, respectively. Label-free, in-situ and very sensitive electrical detection of CRP was demonstrated with the prepared SiNW FET.
Keywords: SENSOR ARRAYS; LABEL-FREE; ELECTRICAL DETECTION